THE ROLE OF NOSTALGIA PRONENESS IN THE EFFECT OF BRAND IMAGE, CORPORATE IMAGE, BRAND TRUST AND CONSUMER INVOLVEMENT ON EMOTIONAL ATTACHMENT: GLOBAL VS. LOCAL BRAND - (:unkn) unknown (My University, 2019)
Nostalgia is an ‘‘individual’s desire for the past or a liking for possessions and activities of days gone by’’ (Holbrook, 1993: 245). For the past few decades nostalgia has been widely used in marketing in order to evoke positive feelings. Hence, the aim of this study is to assess the role of nostalgia proneness in the effect of brand image, corporate image, brand trust and involvement on emotional attachment. The conceptual model is tested empirically against consumers of different levels of nostalgia proneness (low/high). Additionally a comparison is made between a global and a local brand. Convenience sampling is used and data are collected from 643 consumers in Istanbul by means of face to face interviews. Multiple regression analyses is used to test the hypotheses. The results shows that all of the independent variables have statistically significant effects on emotional attachment for both levels of nostalgia proneness and for the global and the local brands. However, differences exist for the two samples (low/high nostalgia prone) and the two brands (Çamlıca and Coca Cola) regarding the most effective variables on emotional attachment.

Nostalji, “bireylerin geçmişe duydukları arzu veya geçmiş günlerde yaşananlara ve sahip olunanlara karşı hissedilen hoşlanma” olarak tanımlanmaktadır (Holbrook, 1993, 245). Son yıllarda pazarlama alanında, nostalji, tüketicilerde olumlu duygular uyandırmak amacıyla yaygın olarak kullanılmaktadır. Bu bağlamda, bu çalışmanın amacı marka imajı, kurumsal imaj, marka güveni ve tüketici ilgilenimi’nin duygusal bağlılık üzerindeki etkisinde nostalji’nin rolünü incelemektir. Kavramsal model farklı nostalji eğilimi düzeylerine (yüksek/düşük) sahip tüketiciler açısından test edilmiştir. Ayrıca, bir küresel ve bir yerel marka için model karşılaştırılmıştır. Kolayda örnekleme ve yüzyüze anket yöntemi ile İstanbul ilinde 643 anket toplanmıştır. Araştırma hipotezlerini test etmek amacıyla regresyon analizi kullanılmıştır. Araştırma bulgularına göre, her iki marka ve her iki nostalji eğilimi düzeyindeki cevaplayıcı grupları için tüm bağımsız değişkenler duygusal bağlılık bağımlı değişkeni üzerinde istatistiksel olarak anlamlı etki göstermektedir. Ancak, gerek markalar gerek nostalji düzeylerine göre etki dereceleri ve sıralamalarında farklılıklar tespit edilmiştir.
MARKA İMAJI, KURUMSAL İMAJ, MARKA GÜVENİ VE TÜKETİCİ İLGİLENİMİNİN DUYGUSAL BAĞLILIK ÜZERİNDEKİ ETKİSİNDE NOSTALJİ EĞİLİMİNİN ROLÜ: KÜRESEL VE YEREL MARKA KARŞILAŞTIRMASI
Keywords: İktisat; İşletme